Comparative biomechanical analysis of rigid vs. flexible fixation devices for the lumbar spine: A geometrically patient-specific poroelastic finite element study. (November 2021) - Khalaf, Kinda; Nikkhoo, Mohammad
Abstract: Background and Objective: Lumbar spinal stenosis (LSS), or the narrowing of the spinal canal, continues to be the leading preoperative diagnosis for adults older than 65 years who undergo spine surgery. Although the treatment of LSS depends on its severity, the optimal surgical technique towards decreasing the risk of adjacent segment disease (ASD) remains elusive. This study aimed to comparatively analyze spinal biomechanics with rigid and flexible fixation devices (i.e., rigid and dynamic posterolateral fusion (PLF) and interspinous process (ISP) devices) during daily activities. Methods: Using a validated parametric poroelastic finite element modeling approach, 8 subject-specific pre-operative models were developed, and their validity was evaluated. Parametric FE models of the lumbar spines were then regenerated based on post-operation images for (A) rigid PLF (B) dynamic PLF (C) rigid ISP device (Coflex) and (D) flexible ISP device (DIAM) at L4-L5 level. Biomechanical responses for instrumented and adjacent intervertebral discs (IVDs) were analyzed and compared subject to static and cyclic loading. Results: The preoperative models were well comparable with previous works in literature. The postoperative results for the PLF and Coflex rigid systems, demonstrated greater ROM; higher values of stress and strain in the AF region; and increased disc height and fluid loss at the adjacent levels, as compared with the pre-op models and the post-op results of the flexible systems (i.e., dynamic PLF and DIAM). The calculated forces on the facet joint were of smaller magnitude for the ISP devices as compared to the PLF, particularly during extension. Conclusions: This study demonstrates that the dynamic PLF construct and DIAM implants could be effective to maintain the natural poroelastic characteristics of adjacent IVDs, which could be beneficial for enhancing long-term clinical outcomes. FEM provides clinicians with an invaluable patient-specific quantitative tool for informed surgical planning and discerning follow-up management.